Memory loss associated with viral infection by SARS-CoV-2: Literature review (Research, Society and Development, 2022)
The aim of this article is to review the literature about the neurological symptoms findings of SARS-CoV-2, mainly related to memory loss, to help in a better understanding of the disease and the possible pathophysiological aspects that give rise to it. Articles published from 2020 to 2021 were searched through the PubMed, CAPES, UpToDate and Scielo databases, using the keywords 'Covid-19', 'Memory', 'Brain Fog', 'Long-Hauler', ' SARS-CoV-2', 'Nervous System', 'Cognitive Deficit', 'Coronavirus', Memory-Loss', 'Alzheimer', 'Neuro-Covid', 'Neuro Invasion'. Among the reports of memory loss associated with COVID-19, the most common pathophysiology founded was indirect alteration through inflammatory mechanisms in the CNS, followed by direct alterations in the hippocampus and cortical regions. There was also a description of the “brain frog”, cognitive alterations, headache, sleep disorders, mood alterations, depression and anxiety. The described changes mainly affected long-term patients after the disease recovery process, but acute changes were also reported. The neurological findings of Covid-19 are similar to those founded in other diseases of viral etiology. There is also the possibility of aggravation of pre-existing clinical conditions such as Parkinsonism and Alzheimer's, in addition to comorbidities such as diabetes, hypertension and kidney disease, enabling the worsening of the patients clinical condition. We must also pay attention to the possibility that the initial neural manifestation of the disease is “brain-frog”. Thus, the correlation between memory loss and SARS-CoV-2 requires further studies and its really important for scientific research about neurological findings of the current pandemic.